Who Stays and for How Long: Examining Attrition in Canadian Graduate Programs - DeClou, Lindsay (Canadian Journal of Higher Education, 2017)
Attrition from Canadian graduate programs is a point of concern on a societal, institutional, and individual level. To improve retention in graduate school, a better understanding of what leads to withdrawal needs to be reached. This paper uses logistic regression and discrete-time survival analysis with time-varying covariates to analyze data from the Youth in Transition Survey. The pre-entry attributes identified in Tinto’s (1993) model of attrition are examined to help uncover who is most likely to withdraw from graduate school. A good academic background is shown to be the strongest predictor of entering graduate school. Upon entry, demographic and background characteristics, such as being married and having children, are associated with a reduced likelihood of completing. Policy recommendations at the department and institution level are provided as well as directions for future research.